Effect of sacubitril/valsartan on the hypertensive heart in continuous light-induced and lactacystin-induced pre-hypertension: Interactions with the renin-angiotensin-aldosterone system - Simko, Fedor; Stanko, Peter; Repova, Kristina; Baka, Tomas; Krajcirovicova, Kristina; Aziriova, Silvia; Domenig, Oliver; Zorad, Stefan; Adamcova, Michaela; Paulis, Ludovit (Biomedicine & pharmacotherapy, 2024)
This study investigated whether sacubitril/valsartan or valsartan are able to prevent left ventricular (LV) fibrotic remodelling and dysfunction in two experimental models of pre-hypertension induced by continuous light (24 hours/day) exposure or by chronic lactacystin treatment, and how this potential protection interferes with the renin-angiotensin-aldosterone system (RAAS). Nine groups of three-month-old male Wistar rats were treated for six weeks as follows: untreated controls (C), sacubitril/valsartan (ARNI), valsartan (Val), continuous light (24), continuous light plus sacubitril/valsartan (24+ARNI) or valsartan (24+Val), lactacystin (Lact), lactacystin plus sacubitil/valsartan (Lact+ARNI) or plus valsartan (Lact+Val). Both the 24 and Lact groups developed a mild but significant systolic blood pressure (SBP) increase, LV hypertrophy and fibrosis, as well as LV systolic and diastolic dysfunction. Yet, no changes in serum renin-angiotensin were observed either in the 24 or Lact groups, though aldosterone was increased in the Lact group compared to the controls. In both models, sacubitril/valsartan and valsartan reduced elevated SBP, LV hypertrophy and fibrosis and attenuated LV systolic and diastolic dysfunction. Sacubitril/valsartan and valsartan increased the serum levels of angiotensin (Ang) II, Ang III, Ang IV, Ang 1-5, Ang 1-7 in the 24 and Lact groups and reduced aldosterone in the Lact group. We conclude that both continuous light exposure and lactacystin treatment induced normal-to-low serum renin-angiotensin models of pre-hypertension, whereas aldosterone was increased in lactacystin-induced pre-hypertension. The protection by ARNI or valsartan in the hypertensive heart in either model was related to the Ang II blockade and the protective Ang 1-7, while in lactacystin-induced pre-hypertension this protection seems to be additionally related to the reduced aldosterone level.
Keywords: Stroke Volume; aminobutyráty; Animals; Remodelling; Prehypertension; hypertenze; Hypertrophy, Left Ventricular; Rats, Wistar; hypertrofie levé komory srdeční; fixní kombinace léků; Angiotensin/aldosterone; Fibrosis; Renin; Heart Failure; Pre-hypertension; Continuous light; srdeční selhání; Tetrazoles; aldosteron; renin-angiotensin systém; Sacubitril/valsartan/ARNI; Renin-Angiotensin System; Lactacystin; acetylcystein; tetrazoly; Valsartan; Hypertension; Male; Aldosterone; valsartan; bifenylové sloučeniny; tepový objem; Aminobutyrates; krysa rodu Rattus; mužské pohlaví; zvířata; Biphenyl Compounds; prehypertenze; fibróza; renin; Rats; Drug Combinations; potkani Wistar; Acetylcysteine